Preface: 3rd International Conference on Business Management, Marketing and Foreign Trade (BMMFT 2024) - Timothy, Anastasia; Zhao, Gang (Transactions on Economics, Business and Management Research, 2024)
The 2024 3rd International Conference on Business Management, Marketing and Foreign Trade (BMMFT 2024) has been held during October 19-20, 2024, in Frankfurt, Germany. BMMFT 2024 aims to provide an excellent interdisciplinary platform for researchers, practitioners, and educators to show and discuss the latest trends and concerns in the fields of economics, business, marketing management, and foreign trade, as well as the practical challenges encountered and solutions adopted.The key intention of BMMFT 2024 is to provide opportunity for the global participants to share their ideas and experience in person with their peers expected to join from different parts of the world. In addition, this gathering will help the delegates to establish research and/or business relations and linkage for future collaborations in their career path. We look forward to seeing you again next year.The Committees of BMMFTFrankfurt, Germany